2015
DOI: 10.12784/nzcomjnl51.2015.4.23-29
|View full text |Cite
|
Sign up to set email alerts
|

Clinically overweight and obese mothers and low rates of breastfeeding: Exploring women's perspectives

Abstract: Background: It is universally recognised that breastmilk is the best food for babies and that breastfeeding provides significant health benefits for both mothers and babies. Women who are overweight or obese have lower rates of initiation and duration of breastfeeding. There is a need to understand the woman's perspective, and any additional factors that may contribute to breastfeeding difficulties for overweight or obese women.Objective: The aims of this research were to explore the breastfeeding experiences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Quantitative and qualitative studies reported physical barriers including larger breasts, bigger areolas, and additional body tissue made infant handling and breastfeeding positions such as cradle or cross cradle more difficult (Claesson, Larsson, Steen, & Alehagen, ; Garner et al, ; Jarlenski et al, ; Massov, ). Jarlenski et al () found that significantly more women with obesity (26.5%) than without obesity (21.0%; p < .05) reported “baby had trouble sucking or latching on” as a reason for not breastfeeding to 6 months (Jarlenski et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Quantitative and qualitative studies reported physical barriers including larger breasts, bigger areolas, and additional body tissue made infant handling and breastfeeding positions such as cradle or cross cradle more difficult (Claesson, Larsson, Steen, & Alehagen, ; Garner et al, ; Jarlenski et al, ; Massov, ). Jarlenski et al () found that significantly more women with obesity (26.5%) than without obesity (21.0%; p < .05) reported “baby had trouble sucking or latching on” as a reason for not breastfeeding to 6 months (Jarlenski et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Finding nursing bras to fit was also identified as a problem for them. Additionally, Massov () reported women's concerns that as their breasts were heavy, they were worried they would suffocate their infant by “squishing” them.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations